BIOLOGY SCIENCE CHALLENGES AND IMPACT FOR HUMAN HEALTH IN INDIA - Dr. Renuka Deshmukh, Dr. Sudarshana Borah, Dr. R. Malathi, Dr Sandeep Rout, Dr. Sunita Dhote, Anu Swedha Ananthan, (Chelonian Research Foundation, 2023)
India's biological sciences are confronted with a variety of complex issues that collectively affect public health. Significant threats to public health are posed by increased rates of infectious diseases, environmental deterioration, and rapid population growth. Air pollution exacerbates respiratory illnesses, while limited access to clean water and sterilisation increases the prevalence of waterborne illnesses. Moreover, the rise in anti-toxin blockage is a fundamental issue that affects the viability of medications for incurable illnesses. Addressing these issues calls for a comprehensive approach that combines cutting edge research, environmentally friendly medical procedures, and educational campaigns to increase public attention. Despite these obstacles, advances in genomics and biotechnology promise bright paths towards personalised medicine, illness prognosis, and improved healthcare outcomes. Collaborative efforts among academics, the government, and the private sector are essential to overcoming these challenges and promoting a healthier future for the Indian populace. Keywords: Biology Science, Human Health, Sustainable Healthcare Practices, Public Health, Environmental Degradation, Rapid Population Growth, Air, Water, Pollution-Related, Health Challenges